Adsorpsi Zat Warna Methylene Blue Menggunakan Spent Bleaching Earth Sebagai Adsorben - Tejo Yulandi; Edy Saputra; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The industrial waste especiallytextile waste is one of the causes of environmental problems that require effective and efficient processing. Adsorption is a separation method that is simple, easy to operate, flexible, affordable cost and does not produce toxic products. The purpose of this study calculates the efficiency of decreasing the concentration of the colors contained in metyhlene blue dye and studying the adsorption capacity to variations in pH, adsorbent mass and stirring time. The maximum wavelength of the dye methylene blue 660 nm. The efficiency of 99.973 % decline in the highest concentration. Isotherm corresponding to methylene blue dye adsorption by spent bleaching earth is Langmuir isotherm with adsorption capacity to variations in pH of 0.5035 mg/g, the adsorbent mass variation of 0.3816 mg/g, the stirring time variation of 0.5012 mg/g.Keywords : Adsorption, Methylene Blue, Spent Bleaching Earth, EfficiencyDecreased Concentration, Adsorption Capacity